2022
DOI: 10.2478/bhk-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between differing magnitudes of inter-limb asymmetry and linear and change of direction speed performance in male youth soccer players

Abstract: Study aim: This study examines the relationship between different magnitudes of asymmetry and their effects on speed performance. Material and methods: Forty-two sub-elite male youth soccer players performed a 30-m sprint, change of direction, single leg countermovement jump and single leg hop. Subjects were divided into groups with vertical and horizontal asymmetry, and both groups were then divided into three groups according to magnitudes of inter-limb asymmetry (<5%, 5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…We also report distinct bilateral asymmetries compared to observations in similar soccer population. 6,9 For example, most of young sub-elite male soccer players (22 out of 42) had a bilateral asymmetry above 10%. 6 Taking these results into account, it‘s possible that soccer players can be more predisposed to various injuries during high-intensity activities (e.g., cutting and landings), because of additional stress placed on the weaker leg due to bilateral asymmetry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also report distinct bilateral asymmetries compared to observations in similar soccer population. 6,9 For example, most of young sub-elite male soccer players (22 out of 42) had a bilateral asymmetry above 10%. 6 Taking these results into account, it‘s possible that soccer players can be more predisposed to various injuries during high-intensity activities (e.g., cutting and landings), because of additional stress placed on the weaker leg due to bilateral asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 For example, most of young sub-elite male soccer players (22 out of 42) had a bilateral asymmetry above 10%. 6 Taking these results into account, it‘s possible that soccer players can be more predisposed to various injuries during high-intensity activities (e.g., cutting and landings), because of additional stress placed on the weaker leg due to bilateral asymmetry. 5 Indeed, in young elite team-sports athletes those more predisposed to injury had single leg countermovement bilateral asymmetry considerably above 10% cut-off criterion (mean CMJ ASY = 16.98%) compared with non-injured counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normative data from Hoch and McKeon 38 report interlimb asymmetries of 1-2cm in 35 healthy participants and Rabin et al 39 found asymmetries of 10° in 23% of male military recruits. Arede et al 40 and Işın et al 41 report frequent asymmetries of over 10% in male soccer players but argue that differences occur due to the functional demands of the sport. However, in comparison, other authors have found no asymmetry in DFROM, 42,43 but this could be due to methodological differences between the studies and how asymmetry has been calculated.…”
Section: Introductionmentioning
confidence: 99%